Development of a Web-Based Training Administration Information System at PT ZAF International - Muhammad Fahmi; Septiano Alvian Ismau; Yasin Kamil; Sutriyono Sutriyono (Journal Majelis Paspama, 2026)
PT ZAF International is a training institution that provides various training programs for the community. Previously, the training administration process utilized Google Forms for participant registration and spreadsheets for data management. The use of separate applications made the administrative process less efficient, required more time for data processing, and increased the risk of errors in assigning Participant Identification Numbers (NIP) and managing participant records. This internship aimed to design and develop a Web-Based Training Administration Information System to improve the administrative process at PT ZAF International. The system was developed using the Waterfall software development method, which consists of the requirements analysis, system design, implementation, testing, and maintenance stages. The application was built using the Laravel framework with PHP as the programming language and MySQL as the database management system. System testing was conducted using the Black Box Testing method to ensure that all system functions operated according to the specified requirements. In addition, User Acceptance Testing (UAT) was carried out to evaluate the system's acceptance by the end user. The result of this internship is a web-based information system that provides features for participant registration, registration data management, participant management, training management, training categories, training batches, referral management, and user management. The system is also capable of generating Participant Identification Numbers (NIP) automatically, thereby reducing the manual work previously performed by the administrator. Based on the testing results, all system functions operated successfully, and the system was considered capable of improving the efficiency and effectiveness of the training administration process while facilitating data management at PT ZAF International.